Factors influencing the inclination of settlers hiring contract workers for oil palm FFB harvesting in Felda Kerteh, Dungun,Terengganu / Nour Aina Mardhia Ibrahim - Ibrahim, Nour Aina Mardhia (Faculty of Plantation and Agrotechnology, 2015)
In Malaysia, oil palm planted area has been increasing rapidly since 1960. A large number of labors require working under plantation because of development of plantation sector. The big problem facing by Malaysian plantation is labor shortage. In harvesting of fresh fruit bunch involve harvester, collector and transportation. Smallholders like settler prefer hiring contract workers to do harvesting, collecting, transporting and other task. Contract workers consist of local workers and foreign workers. The settlers have to pay high charges to pay the contract workers. There are many factors that influencing inclination settlers hiring contract worker for instance age factor, health status, labor shortage, financial, lack of skills and lack of interest from young generations and others. So, this study is done to identify the factors that contribute settlers hiring contract workers especially in harvesting oil palm FFB. or why settlers prefer to hire contract workers than done on its own. This case study has been done in Felda Kerteh 1 in Dungun, Terengganu. From the survey area, the totals of respondent are 400 peoples. According to Israel (1992), the samples will be taken are 135 peoples from 400 peoples as the respondents in this case study. The respondents are randomly selected to avoid bias and make it easier. Questionnaire will be used the method to collect the data and face to face interviews have been carried out in this study. Data were subjected to be descriptive analysis and test using SPSS software. This study conducted at the end of June 2014 until September 2014.